DISTRIBUSI FILARIASIS LIMFATIK I DI KELURAHAN PABEAN, KECAMATAN PEKALONGAN UTARA KOTA PEKALONGAN, PROVINSI JAWA TENGAH - Sunaryo Sunaryo; Tri Ramadhani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2008)
Lymphatic filariasis still occurs to be a health problem in Pekalongan City. Pabean village, North Pekalongan SubDistrict up to now. This area lays between two filariasis endemic areas, that is Bandengan village North Pekalongan SubDistrict (Mf-rate: 2,38 %) and Pasirsari village, West Pekalongan Sub-District (Mf-rate: 2,34%). The aim of the study was to determine the lymphatic filariasis distribution, based on place, people and time, the chronic and a cute cases, the density of microfilaria and microfilaria periodicity. This research used an observational study with cross sectional design. Clinical and parasitological surveys conducted to 500 persons, screened using a 60 pi off inger prick blood which should be dried on a slide, stained and examined under a microscope based on the standard procedure. The periodicity survey conducted to the people whose proven to be positive microfilaria for every two hours. The result found 17 people with positive microfilariae (mf-rate: 3,4%). The agent of lymphatic filariasis in Pabean village was Wuchereria bancrofti, type, with density of microfilaria between 3 to 72 if this species is nocturnal periodic which circulate mostly around 10.00 a.m. Lymphatic filariasis were found in RW III (7 cases) and RW II (2 cases) withaverage age > 50 years old. Therefore to overcome this problem the community need to have Mass Drug Administration (MDA).